Lost in Babylon - Lerangis, Peter, (Lerangis, Peter. Seven wonders ;, 2013)
Journeying to the ancient city of Babylon when Bhegad tracks down Marco, the companions face a daunting choice involving a dire trap and a long-lost figure from Jack's past.